The sqrt of (34 m^4) is sqrt(34) times sqrt(m^4).
The sqrt of m^4 is easy ... that's just m^2 .
The other part is more messy. There's not much you can do with it.
sqrt(34) = sqrt(17) times sqrt(2).
That doesn't help make it any simpler.
You might as well just leave it as sqrt(34).
Then the final, simplified form of the original expression is
m^2 sqrt(34)
Y - 2 = -3/4 (x - 6)
y = -3/4 (x - 6) + 2
When, x = -2,
y = -3/4 (-2 - 6) + 2 = -3/4 (-8) + 2 = 6 + 2 = 8
One point is (-2, 8)
When, x = 2,
y = -3/4 (2 - 6) + 2 = -3/4 (-4) + 2 = 3 + 2 = 5
Another point is (2, 5)
Answer: 26
Step-by-step explanation:
A fraction could be -3 1/6
I believe it is the last that is highlighted in yellow